Opportunities and challenges of global health diplomacy for prevention and control of noncommunicable diseases: a systematic review - Mohsen Asadi-Lari; Ahmad Ahmadi Teymourlouy; Mohammadreza Maleki; Mahnaz Afshari (BMC, 2021)
Abstract Background and aim The growing globalization has changed the goals and methods of diplomacy. Due to the challenges and complexities of dealing with noncommunicable diseases (NCDs) at the national and international levels, policy makers require global health diplomacy (GHD) to achieve the goals of prevention and control of NCDs. The purpose of this systematic review was to identify the challenges and opportunities in GHD for NCDs. Methods A systematic review of articles was conducted by searching MEDLINE via PubMed, Web of Science, Scopus, and Embase and by using Google and Google Scholar search engines. Additional articles were identified by reviewing reference lists and a number of special journals. The inclusion criteria include literature published in English from 2007 to 2020, and the exclusion criteria are literature published in any language other than English, absence of full text, dissertations, and duplicates. Overall, 32 articles met the requirements for inclusion in this review and were analyzed using content analysis in MAXQDA 10. Findings There are 32 published articles on GHD for NCDs. Identified challenges were classified into three levels: global (global health governance), national (Governance at the state level, health sector, and civil society), and industry. The progress on global health issues has created opportunities for the development of GHD for the prevention and control of NCDs. These opportunities were divided into three levels: international, national, and individual level. Conclusion Various challenges at the global level, national level, and industry led to less engagement of policymakers in GHD for prevention and control of NCDs and, as a consequence, a less coordinated approach to address prevention and control of NCDs worldwide. So, there is a need for more efforts of collective action and negotiation for tackling NCDs. Policymakers and managers of the health system should increase the advocacy, building a coalition with civil society, use negotiation and diplomacy to engage with other sectors and organizations, manage industry conflicts, and leverage foreign policy to promote health and welfare.